Probability of sinus rhythm conversion and maintenance in cardiac resynchronization therapy patients with atrial fibrillation during 5‐year follow‐up. (20th July 2020) - Ziegelhoeffer, Tibor; Pecha, Simon; Rahmani, Rilind; Thaqi, Nobel; Ackermann, Xenia; Hakmi, Samer; Choi, Yeong‐Hoon; Burger, Heiko
Abstract: Introduction: There is a high prevalence of atrial fibrillation (AF) in patients with heart failure presented for cardiac resynchronization therapy (CRT). It remains unclear whether an atrial lead should be implanted in these patients. We, therefore, analyzed outcomes and course of rhythm in AF patients undergoing CRT implantation during long‐term follow‐up. Methods and Results: Between 2004 and 2018, 328 consecutive patients with a history of AF receiving CRT implantation were included in this study. 132 patients had preoperatively paroxysmal AF (px‐AF), while 70 and 126 patients had persistent AF (ps‐AF) and long‐standing persistent AF (lp‐AF), respectively. The outcome data were collected in our institutional database and analyzed retrospectively. Two hundred and seventy‐seven patients received an atrial lead at the time of implantation, nine during follow‐up. No major lead implantation‐associated complications were observed. In patients with px‐AF, sinus rhythm (SR) was present in 78.8% at admission, 95.5% ( p < .001) at discharge, and 85.7% ( p = .965) after 5 years. In ps‐AF patients SR was present in 28.6%, 91.4% ( p < .001) and 69.7% ( p < .001), while all lp‐AF patients showed AF at admission and had SR rate of 50.8% ( p < .001) at discharge and 44.1% after 5 years ( p < .001). Conclusion: We observed a high rate of conversion and long‐term persistence of SR in AF patients undergoing CRT implantation. Due to the low rate of lead implantation‐associated complications and the high successful SR conversion rates, we recommend the implantation of an atrial lead in CRT patients with AF.